2015
DOI: 10.12973/eurasia.2016.1422a
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Different Teaching Designs of ‘Acids and Bases’ Subject

Abstract: Inability to link the acid-base concepts with daily life phenomena (as contexts) highlights the need for further research on the context-based acid-base chemistry. In this vein, the aim of this study is to investigate the effects of different teaching designs (REACT strategy, 5Es learning model and traditional (existing) instruction) relevant with 'acids and bases' subject on pre-service science teachers' conceptions and attitudes towards chemistry and to compare them with each other. Within quasi-experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…29,30 Additionally, Ü ltay and Calik found that pre-service chemistry teachers held the misconception that water cannot act as an acid or a base because it acts as a solvent. 31 Schmidt identified several misconceptions about acids and bases. 32 One misconception was that acids must hold a positive charge and that bases must hold a negative charge; thus the misconception follows that neutral compounds, e.g., water, are neither an acid nor a base.…”
Section: Student Understanding Of Acid-base Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 Additionally, Ü ltay and Calik found that pre-service chemistry teachers held the misconception that water cannot act as an acid or a base because it acts as a solvent. 31 Schmidt identified several misconceptions about acids and bases. 32 One misconception was that acids must hold a positive charge and that bases must hold a negative charge; thus the misconception follows that neutral compounds, e.g., water, are neither an acid nor a base.…”
Section: Student Understanding Of Acid-base Modelsmentioning
confidence: 99%
“…3,26,27 Additionally, understanding water's ability to act as both an acid and a base can improve student's overall understanding of Lewis acids and bases. [28][29][30][31]33…”
Section: Student Understanding Of Acid-base Modelsmentioning
confidence: 99%
“…Phrased differently, the research results indicated that the interdisciplinary mathematical modeling tended to support contextual learning (context-based learning) and higher-order thinking skills (e.g., problem solving, 21 st century skills, mathematical thinking, reasoning abilities, creative thinking, and scientific literacy). Further, it challenged the abstractness and rote learning of school mathematics and science (Cedere et al, 2020;Davison et al 1995;Doğan et al, 2019;Ültay & Çalik, 2016). Hence, it attempted to enhance the seventh-grade students' familiarity with the interdisciplinary mathematical modeling and environmental issues.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Ultay and Calik (2016) examined the effects of different teaching strategies (REACT strategy, 5E learning model, and traditional teaching) for the topic of acid-base in chemistry courses on science teacher candidates' concepts. In the research, a case for acid rains has been developed, and it was concluded that the REACT strategy was effective in teacher candidates' retention of the concepts in their long-term memories.…”
Section: Introductionmentioning
confidence: 99%